2007
DOI: 10.1111/j.1742-7843.2007.00079.x
|View full text |Cite
|
Sign up to set email alerts
|

Trifluralin Toxicity in a Chagas Disease Mouse Model

Abstract: Even though trifluralin ( α , α , α -2,6-dinitro-N-N-dipropyl-p-toluidine) is effective for the treatment of experimental Chagas disease, more preclinical toxicity studies need to be performed. Cell toxicity of trifluralin was studied in Hep-G2 and Vero C76 cells treated with 50 and 150 µ M trifluralin. The results show that duplication time, amount of cellular protein and cell protein/DNA values were normal. Histological, haematological and chemical parameters were measured in CF1 mice after oral trifluralin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…The viability of HuWa TERT cells was clearly impacted by exposure to all selected environmental contaminants (Figure a), with EC 50 ranging from 6.0 (lindane) to 173.3 nM ( p,p’ -DDE); in order of increasing toxicity: lindane > chlorpyrifos > dieldrin > endosulfan > trifluralin > p,p’ -DDE. Each of our priority pesticides have been applied in lethal ecotoxicological studies with a variety of species. Our observed DAPI EC50 values were consistent with the reported LC50 on several marine fish species for lindane (ranged 3.8 to 226 nM), chlorpyrifos (ranged 0.7 to 5 × 10 5 nM), dieldrin (ranged 2.6 to 207.4 nM), endosulfan (ranged 0.24 to 368.6 nM), , and trifluralin (ranged 25 to 2.2 × 10 6 nM) . To our knowledge, no in vitro cytotoxicity studies have reported on cetaceans for our candidate chemicals, with the exception of p,p’ -DDE.…”
Section: Resultssupporting
confidence: 81%
“…The viability of HuWa TERT cells was clearly impacted by exposure to all selected environmental contaminants (Figure a), with EC 50 ranging from 6.0 (lindane) to 173.3 nM ( p,p’ -DDE); in order of increasing toxicity: lindane > chlorpyrifos > dieldrin > endosulfan > trifluralin > p,p’ -DDE. Each of our priority pesticides have been applied in lethal ecotoxicological studies with a variety of species. Our observed DAPI EC50 values were consistent with the reported LC50 on several marine fish species for lindane (ranged 3.8 to 226 nM), chlorpyrifos (ranged 0.7 to 5 × 10 5 nM), dieldrin (ranged 2.6 to 207.4 nM), endosulfan (ranged 0.24 to 368.6 nM), , and trifluralin (ranged 25 to 2.2 × 10 6 nM) . To our knowledge, no in vitro cytotoxicity studies have reported on cetaceans for our candidate chemicals, with the exception of p,p’ -DDE.…”
Section: Resultssupporting
confidence: 81%
“…These concentrations were chosen according to their 50% inhibitory concentration (IC 50 ) and toxicity levels. [24][25][26][27] The cells were incubated for 24 hours and harvested from the wells and centrifuged at 1200 rpm for 5 min.…”
Section: Cell Culture and Treatmentmentioning
confidence: 99%
“…Recent research has found that it is toxic to fish and aquatic invertebrates (Turgut 2007;Winkaler et al 2007;Zaidenberg et al 2007). Trifluralin has been implicated increasingly in mammalian toxicity (Fennell et al 2006) and genotoxicity (Gebel et al 1997;Fernandes et al 2007).…”
Section: Introductionmentioning
confidence: 99%